South Pacific Land Law: Some Regional Challenges, Cases and Developments - Farran, Sue (Victoria University of Wellington Law Review, 2001)
Land in the South Pacific is largely regulated by introduced English Common Law. However, the vast bulk of the land in the region is held under different forms of customary land tenure, and the perceptions of land and its use are distinctly regional. In this article, the author considers how the Common Law has been adapted in the region to accommodate and reflect customary law and practice. Selected cases from the region are used to highlight the difficulties that the courts face in blending Common Law principles with customary practice and accommodating changing uses of land that challenge traditional solutions.